Corporate social responsibility and financial performance: does CSR strategic integration matter? - Deepa Sharma; Suman Chakraborty (Cogent Business & Management, 2024)
This study aims to analyse the relationship between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP) of Indian firms with the moderating role of CSR strategic integration on the relationship. This study examined a sample of 134 manufacturing firms listed on the National Stock Exchange of India from 2011 to 2021. The authors used a random effects panel regression model to study how CSR strategic integration affects the CSR-CFP relationship. The findings of this study show a significantly negative impact of CSR on CFP. Regarding the moderating effect, a positive interaction of CSR strategic integration is found, which means that the relationship between CSR and CFP is strengthened when CSR is undertaken by businesses that consider the goals of a firm. The study suggests that different measures of CSR strategic integration can be used in future studies, and market-based financial performance measures can be additionally used to test these relationships. The study contributes to the literature concerning CSR-CFP relationship by taking CSR strategic integration as the moderating variable, which is a novel idea. This study also provides suggestions to companies and policymakers who can incorporate strategic considerations in the business case of CSR, which will create positive outcomes for both companies and society.
Keywords: 650; Corporate social responsibility; financial performance; moderation effect; CSR strategy integration; India; fixed effects; strategy